2020
DOI: 10.1038/s41528-020-00086-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive electrolyte-assisted temperature sensor

Abstract: Heat sensors form an important class of devices that are used across multiple fields and sectors. For applications such as electronic skin and health monitoring, it is particularly advantageous if the output electronic signals are not only high, stable, and reproducible, but also self-generated to minimize power consumption. Here, we present an ultrasensitive heat sensing concept that fulfills these criteria while also being compatible with scalable low-cost manufacturing on flexible substrates. The concept re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…The TiN absorber was to generate heat under light illumination and the substrate was used as a heat sink. The LiTS could exhibit a huge advantage of high-temperature sensitivity over the commercial K-type thermocouple 56 with a temperature sensitivity of 0.04 mV K −1 . When the lamp is turned on, the voltage was suddenly generated by the LiTS and varied from −17.5 to −90 mV within the 50 s (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TiN absorber was to generate heat under light illumination and the substrate was used as a heat sink. The LiTS could exhibit a huge advantage of high-temperature sensitivity over the commercial K-type thermocouple 56 with a temperature sensitivity of 0.04 mV K −1 . When the lamp is turned on, the voltage was suddenly generated by the LiTS and varied from −17.5 to −90 mV within the 50 s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the limiting factor for the speed of the i -TE LiTS is the bulk TE component, further miniaturization of the basic TE voltage generating unit will allow much shorter response times, which will be demonstrated in our future work. Overall, the i -TE based system provides higher voltage signals for the same thermal stimulus, which not only improves the resolution of the detector but also benefits from absolute large changes in voltage, especially for the heat-gated transistors, heat mapping 56 , 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Here, the device detects the temperature variation and works as a temperature sensor having a negative dependence characterized by a voltage sensitivity 𝑚 = ∆𝑉 ∆𝑇 ⁄ , where ∆𝑉 is the variation in the output electrical signal. Several authors report, in the literature, temperature sensors based on natural biopolymers, obtained from renewable resources (such as cellulose, silk, chitosan and tobacco cells) that are electrically biased [1,39] or self-powered [8] with a negative voltage sensitivity. In this latter case, the thermal-to-electric conversion mechanism is achieved through the thermogalvanic, or Soret, effect [34,40].…”
Section: Temperature Dependence Of Electrical Characteristicsmentioning
confidence: 99%
“…Recently, electrolytes based on hydrogel have been extensively investigated due to their conductive ionic properties and capability to form a galvanic cell with metal electrodes. Jonsson et al reported an electrolyte-assisted temperature sensor (operating within a variation of 15 • C) based on a hydrogel with a negative voltage sensitivity of about 11 mV/K [8]. Moreover, Ortega et al described a self-powered smart patch for sweat conductivity monitoring where the body fluid acts as the battery electrolyte [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, to obtain better temperature measurement performance, new materials such as graphene, , carbon nanotubes (CNTs), , and metal nanowires , were employed as the temperature-sensing material. By combining these materials with flexible substrates, many high-performance flexible temperature sensors have been developed. However, most of these flexible sensors are in the form of an electrical-signal-based sensor, which needs a wired connection or the installation of an additional wireless signal transmitter . Internal power is also usually needed for these flexible temperature sensors .…”
Section: Introductionmentioning
confidence: 99%